Physiological Responses on Krabi-Krabong Skill Learning in Students of Buriram Province - Amorntheap Wandee; Ban Chabairam; Suchart Homjan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aimed to analyze the electromyographic (EMG) responses during Mai Ram Krabi-Krabong and striking techniques from an exercise physiology perspective, and to compare physiological responses in students of Buriram province who received Krabi-Krabong training and those who did not. The study was conducted in two phases: the first examined EMG responses during Krabi-Krabong techniques, while the second developed and studied the effects of Krabi-Krabong instruction in physical education classes. The study involved two groups of participants. The first group in study 1 consisted of 16 university students skilled in Krabi-Krabong techniques, who participated in the EMG analysis. The second group in study 2 comprised 50 high school students, divided equally into a control group receiving standard physical education instruction and an experimental group receiving Krabi-Krabong training. Both groups participated in weekly 50-minute sessions for 12 weeks. Assessments included computerized cognitive tests, and physical fitness tests.